Fear of Cancer Recurrence and its Predictive Factors among Iranian Cancer Patients - Aghdam, Alireza Mohajjel (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: Fear of cancer recurrence (FOCR) is one of the most important psychological problems among cancer patients. In extensive review of related literature there were no articles on FOCR among Iranian cancer patients. AIM: The aim of present study was to investigation FOCR and its predictive factors among Iranian cancer patients. MATERIALS AND METHODS: In this descriptive-correlational study 129 cancer patients participated. For data collection, the demographic checklist and short form of fear of progression questionnaire was used. Logistic regression was used to determine predictive factors of FOCR. RESULT: Mean score of FOCR among participants was 44.8 and about 50% of them had high level of FOCR. The most important worries of participants were about their family and the future of their children and their lesser worries were about the physical symptoms and fear of physical damage because of cancer treatments. Also, women, breast cancer patient, and patients with lower level of education have more FOCR. DISCUSSION: There is immediate need for supportive care program designed for Iranian cancer patients aimed at decreasing their FOCR. Especially, breast cancer patients and the patient with low educational level need more attention.